2012
DOI: 10.3109/14767058.2012.703719
|View full text |Cite
|
Sign up to set email alerts
|

Maternal mortality from cardiac disease in Turkey: a population-based study

Abstract: The main cause of indirect maternal death has been cardiac disease in 3-year period.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 10 publications
2
16
0
Order By: Relevance
“…Anaemia was the most common indirect cause of SMO in this current analysis. This is in accordance with other reports from developing countries; however, cardiac disease was the leading indirect cause of MD from developed countries …”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Anaemia was the most common indirect cause of SMO in this current analysis. This is in accordance with other reports from developing countries; however, cardiac disease was the leading indirect cause of MD from developed countries …”
Section: Discussionsupporting
confidence: 93%
“…Recent reports indicated that indirect causes were responsible for about a quarter of all maternal deaths . The main indirect causes included anaemia, cardiac disease, HIV/AIDS, and cerebrovascular disease . In 2009, WHO, through an international consultative process, developed a standard definition of maternal near miss, using markers of organ dysfunction during pregnancy, childbirth, or after birth .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study revealed that overall maternal near miss ratio was 2.47 per 1,000 live births and the maternal mortality ratio was 13.46 per 100,000 live births which was below the ratio of Turkey in 2007-2009 periods (19.7 per 100.000 live births) (6). As one of the largest public hospital in the country, the hospital handles about 17.000 deliveries annually.…”
Section: Discussionmentioning
confidence: 55%
“…In their study of maternal mortality in the United States between 2011 and 2013, Creanga et al (14) found that cardiovascular diseases was the leading cause of mortality (15.5%) and 11% of patients with cardiomyopathy had died. In our country, Engin Üstün et al (17) studied cardiac-induced maternal deaths and they found that maternal mortality rate as 19.7 in 100000 live births. Although the main cause of death of these cases was hemorrhage, while in 16.5% the main cause of death was due to cardiac causes and valvular heart disease (25.6%) was the most common cause of cardiac disease.…”
Section: Discussionmentioning
confidence: 99%